Slavery and bonded labor in Asia, 1250-1900 - Allen, Richard Blair (Brill, 2022)
"Slavery and Bonded Labor in Asia, 1250-1900 is the first collection of studies to focus on slavery and related forms of labor throughout Asia. The 15 chapters by an international group of scholars assess the current state of Asian slavery studies, discuss new research on slave systems in Asia, identify avenues for future research, and explore new approaches to reconstructing the history of slavery and bonded labor in Asia and, by extension, elsewhere on the globe. Individual chapters examine slavery, slave trading, abolition, and bonded labor in places as diverse as Ceylon, China, India, Korea, the Mongol Empire, the Philippines, the Sulu Archipelago, and Timor in local, regional, pan-regional, and comparative contexts"
Keywords: Geschichte 1250-1900; Leibeigenschaft; Sklaverei; Asien; Slavery / Asia / History; Peonage / Asia / History; Konferenzschrift -- 2017 -- Leiden